Professionally Important Qualities of Inspectors in the State Small Vessels Inspectorate of EMERCOM of Russia - Julia S. Shoigu; Anastasia A. Tarasova (Rossijskij psihologičeskij žurnal., 2017)
Introduction. Recently, considerable attention has been paid to studying various kinds of professional activities. However, psychological studies on professional activities of inspectors in the State Small Vessels Inspectorate (SSVI) of EMERCOM of Russia are still lacking. The present study examines professionally important qualities which determine the efficiency of professional activities in this group of specialists. Methods. The study involved 275 inspectors in the SSVI of EMERCOM of Russia residing in various federal subjects of Russia. An expert survey helped to choose psychodiagnostic techniques for studying intellectual, cognitive, and personal characteristics of inspectors in the SSVI of EMERCOM of Russia. The experts comprised 40 persons. The study employed methods for mathematical and statistical treatment of data. Results. The comparison of successful and unsuccessful inspectors in the SSVI of EMERCOM of Russia revealed the professionally important qualities that could predict the efficiency of professional activities in this group of specialists. The professionally important qualities were grouped as follows: (a) intellectual and mnestic, (b) emotional and personal, (c) and motivational and volitional. The level of each professionally important quality was measured by mean scores in the group of successful inspectors. Discussion. The carried out psychological study of professional activity of inspectors in the SSVI of EMERCOM of Russia revealed the professionally important qualities necessary for achieving professional goals. The findings are of great help in improving professional psychological selection and determining the degree of compliance of a candidate’s psychological qualities with the requirements for the specialty.